Faktor-Faktor yang Berhubungan dengan Kepatuhan Pekerja Dalam Melaksanakan Standar Prosedur Kerja di PT Meiyume Indonesia 2019 - Ramdhan Allmiansyah; Agustina Agustina (Jurnal Persada Husada Indonesia, 2019)
Compliance is how much the worker has to obey or undergo the applicable regulations related to work safety. The aim is to find out the factors related to worker’s compliance in implementing standard work procedures at PT Meiyume Indonesia in 2019. The design of this research is descriptive with quantitative approach using cross sectional method. The population in this study were 90 people. The number of samples taken was 50 people selected using accident sampling technique. Data analysis used univariate and bivariate using Chi Square. Study results showed a significant relationship between motivation (P-Value = 0,000), attitude (P-Value = 0.010), rewards and penalties (P-Value = 0.002). Whereas no relationship was found between age, knowledge and length of work. This concluded that there must be a higher motivation, a more positive attitude and rewards and penalties should be more established. The company is recommended to improve structured training on work safety procedures provided directly to workers and monitor their application in work processes.